Polycomb-like 2 (Mtf2/Pcl2) Mediated Epigenetic Regulation of Hematopoiesis and Refractory Leukemia - Maganti, Harinad (Université d'Ottawa / University of Ottawa, 2018)
The Polycomb Repressive Complex 2 (PRC2) epigenetically regulates gene expression by methylating lysine 27 on histone 3 (H3K27me3). While the role of PRC2 core members during hematopoiesis has been elucidated, the role of PRC2 accessory protein, Mtf2, has not been well characterized outside of mouse embryonic stem cells. To investigate the role of Mtf2 in vivo, we created a gene-targeted knockout mouse model. Using this model, we discovered that Mtf2 was a critical regulator of hematopoiesis and its loss within the hematopoietic cells leads to loss of global H3K27me3 levels at the transcriptional start sites (TSS) therefore leading to the overexpression of multiple signalling networks. These findings presented in the first part of my thesis place Mtf2 as a critical regulator of hematopoiesis and expand the role of Mtf2 beyond a canonical accessory PcG protein. While our murine studies revealed that the loss of Mtf2 did not cause leukemia in mice, our studies of MTF2 in human cells demonstrated that MTF2 deficiency within human Hematopoietic Stem and Progenitor Cells (HSPCs) causes a myelo-proliferative phenotype that is reminiscent of pre-leukemia. Furthermore, when we screened MTF2 expression within leukemic stem cell (LSC) enriched CD34+ CD38- cells isolated from primary Acute Myeloid Leukemia (AML) patient samples at diagnosis, we observed that MTF2 is miss-regulated in AML and its loss predicted refractory AML. Using MTF2 knockdown (KD) transcriptomic and ChIP-seq data, we drafted MTF2-PRC2 Gene Regulatory Network (GRN) in human HSPCs and LSC enriched cells. Finally, using the MTF2-PRC2 GRN, we uncovered a direct mechanism by which MTF2 regulates chemoresistance in AML and show that targeting this mechanism via MDM2 inhibitors sensitizes refractory AML to standard induction therapy. These findings presented in second part of my thesis demonstrate MTF2 as a novel prognostic marker for refractory AML and provide a novel therapy that helps target MTF2 deficient refractory AML.
Keywords: Leukemia; Refractory